The GENACIS project: a review of findings and some implications for global needs in women-focused substance abuse prevention and intervention - Wilsnack SC (Dove Medical Press, 2012)
Sharon C WilsnackDepartment of Clinical Neuroscience, University of North Dakota School of Medicine and Health Sciences, Grand Forks, ND, USAAbstract: Gender, Alcohol, and Culture: An International Study (GENACIS) is a collaborative study of gender-related and cultural influences on alcohol use and alcohol-related problems of women and men. Members conduct comparative analyses of data from comparable general population surveys in 38 countries on five continents. This paper presents GENACIS findings that (1) age-related declines in drinking are uncommon outside North America and Europe; (2) groups of women at increased risk for hazardous drinking include women who cohabit, women with fewer social roles, more highly educated women in lower-income countries, and sexual minority women in North America; (3) heavier alcohol use shows strong and cross-culturally consistent associations with increased likelihood and severity of intimate partner violence; and (4) one effect or accompaniment of rapid social, economic, and gender-role change in traditional societies may be increased drinking among formerly abstinent women. These findings have potentially important implications for women-focused intervention and policy. Substance abuse services should include attention to middle-aged and older women, who may have different risk factors, symptoms, and treatment issues than their younger counterparts. Creative, targeted prevention is needed for high-risk groups of women. Programs to reduce violence between intimate partners must include attention to the pervasive role of alcohol use in intimate partner aggression. Social and economic empowerment of women, together with social marketing of norms of abstention or low-risk drinking, may help prevent increased hazardous alcohol use among women in countries undergoing rapid social change. Greater attention to effects of gender, culture, and their interactions can inform the design of more effective prevention, intervention, and policy to reduce the substantial global costs of alcohol abuse in both women and men.Keywords: GENACIS, women, alcohol, substance abuse, international, intervention, prevention